Focused Arterial Anastomotic Assessment in a Novel Univariate Design of a Vertical Rectus Abdominis Muscle Flap in a Pig Model - Fischlin, Claudia; Mbaidjol, Zacharia; Olariu, Radu; Constantinescu, Mihai; Leckenby, Jonathan (Journal of Reconstructive Microsurgery Open, 2017)
Background Microsurgical anastomosis is the basis for free tissue transfer. The goal of this study was to create an animal model that mimics free tissue transfer but would focus on the arterial anastomotic assessment alone, without additional bias of a venous anastomosis.Methods A vertical rectus abdominis musculocutaneous (VRAM) flap based on the left deep superior epigastric artery (DSEA) was raised in six large white pigs. The right DSEA was raised and used as the donor vessel. An arterial end-to-end microsurgical anastomosis was then performed between the right and the left SEA artery. The lateral deep epigastric vein (DIEV) was left intact to drain the flap. Perfusion of the flap was confirmed clinically by laser Doppler and by flowmetry.Results One flap failure was observed in this study that occurred on postoperative day (POD) 5 as a consequence of venous occlusion due to hematoma. There was a significant initial drop in arterial flow across the anastomosis in comparison to preanastomotic flow measurements (p < 0.05); however, this was normalized by the seventh POD (p > 0.05). Flow measurements in the vein significantly increased after the arterial anastomosis was completed and the seventh POD (p < 0.05). Laser Doppler assessment demonstrated adequate tissue perfusion of the skin island flap.Conclusion This modified VRAM flap is a viable procedure to simulate a free flap transfer and assess the arterial anastomosis alone, while maintaining the flap's innate venous drainage. This method can allow the investigation of new arterial anastomosis techniques and devices.
Keywords: microsurgery; anastomosis; free flap; animal model